Familial risks of breast and prostate cancers: does the definition of the at risk period matter? - Brandt, Andreas; Lorenzo Bermejo, Justo; Sundquist, Jan; Hemminki, Kari (European journal of cancer, 2010)
Aim - ‘Being at familial risk’ may have different connotations in studies on familial risk of cancer. The register-based definition of a family history considers individuals with an affected relative at familial risk independently of the family member’s diagnostic time. Alternatively, the individuals are classified to be at familial risk only after the diagnosis date of their relative, relevant to clinical counselling and screening situations. The aim of this study was to compare familial breast and prostate cancer risks according to the two definitions. - Patients and methods - The nationwide Swedish Family-Cancer Database with information on cancers from 1958 to 2006 was used to calculate the hazard ratio of breast and prostate cancers according to family history using Cox regression. Family history was defined considering the number and type of affected relatives and the relative’s diagnostic age, respectively. Individuals were considered at familial risk from their entry to the study or, alternatively, from the diagnostic time of the relative. - Results - Hazard ratios were equal whether individuals were considered at risk independent of the relative’s diagnostic date or only after the relative’s diagnostic date. - Conclusion - These results indicate that studies on familial breast or prostate cancer risk which do not take the relative’s diagnosis date into account are applicable to screening and clinical counselling situations. The estimates according to the register-based definition are based on larger numbers of patients, which may be crucial for analysis of small groups such as families of multiple cases.